Visuomenės mokslų mokslinės informacijos institutas (INION). Jo uždaviniai ir veikla - Zaveckienė, Žiedūnė (Knygotyra, 1981)
The System of Information of Social Sciences is a part of the State System of Scientific — technical Information of the SU. At the head of scientific — information institutions in 1969 there was the founded on the basis of the Social Sciences Fundamental Library the INION.At present the INION Library fulfils the functions of the main depository of literature of Social sciences in the country. There one can find about 7 million copies and even more, about 10 million copies with those taken together in branch officies. They serve the needs of about 30000 permanent readers,INION fulfils about 30000 orders a year, it serves the well known scientists, politicians and statesmen.INION publishes bibliographical guides about new Soviet and foreign literature in 28 series, essay magazines about foreign literature in 9 series, assay magazines about Soviet literature in 7 series it prepares variouz essay works and scientific — analytical works on the most actual problems of social sciences.INION solves the most important questions in automation and mechanization of various information processes not only in the Institute but in the whole system of information of social sciences as well.INION fulfils the coordination and methodical guidance over the information activities not only in our country but in the system at socialist countries as well.In future its tasks are becoming more complicated. It plans to speed up the automation and mechanization of information processes, to improve the coordinational and methodical guidance over various information institutions not only in the system of the Academy of Sciences of the SU but on social sciences on the whole. INION must fulfil the most complicated tasks in a new founded Information System of Social Sciences of the Socialist countries (MISON).